Comparative Effects of Biomass Pre-Treatments for Direct and Indirect Transesterification to Enhance Microalgal Lipid Recovery - Ghasemi Naghdi, Forough; Thomas-Hall, Skye R.; Durairatnam, Reuben; Pratt, Steven; Schenk, Peer M. (Frontiers in Energy Research, 2014)
Microalgal lipid recovery for biodiesel production is currently considered suboptimal, but pre-treatment of algal biomass, the use of solvent mixtures and the positioning of transesterification can lead to increased yields. Here, the effect of various reportedly successful pre-treatments and solvent mixtures were directly compared to each other and combined with direct and indirect transesterification methods using the oleaginous microalga Tetraselmis sp. M8. Microwave and thermal pre-treatments were applied and the total lipid and fatty acid methyl ester (FAME) recoveries were investigated. The application of pre-treatments increased FAME recovery through indirect transesterification when a Soxhlet system was used but they had no significant effect for direct transesterification. Gravimetric analyses of total lipids revealed that lipid recovery was highest when utilizing the chloroform-based Bligh and Dyer extraction method; however, FAME yield was the highest when applying a Soxhlet system utilizing a solvent mixture of hexane–ethanol (3:1). Total lipid recovery did not necessarily correlate with the recovery of FAMEs. The highest FAME recovery was achieved from thermal or microwave pre-treated biomass followed by indirect transesterification through Soxhlet extraction. FAME recovery could be more than doubled (increase of up to 171%) under these conditions. We conclude that a simple thermal pre-treatment (80°C for 10 min) in combination with solvent mixture extraction through indirect transesterification may present a cost-effective and scalable option for large-scale lipid extraction from microalgae.